(untitled) (Prostor, 2025)
The book Praxis of Collective Building: Narratives of Philosophy and Construction applies Yugoslav praxis philosophy to analyse architectural and construction practices. It explores how the building process in New Belgrade, through youth engagement, connected social and political ideologies with material production. Through three narratives, the author examines the role of philosophy and collective engagement in post-war construction and social change.